On fictions and realities, the case of “Tom Clancy´s Ghost Recon: Wildlands” videogame and Bolivia. - González-Sancho, Roy (2021)
In this paper, the video game “Tom Clancey’s Ghost Recon: Wildlands” has been analyzed through a scientific essay departing from the fiction depicted on the setting context: Bolivia. In this way, various contents of this production are studied depending on the political or historical events on which Ubisoft Paris and Ubisoft Milan have based for the design of the game. It is concluded that this production corresponds with the general tendencies of the warlike video games, with the treatment of stereotypes and speeches of the United States exceptionality. in the case of Bolivia, it has been handled with an image of incapacity, defeat, traitors and as a country whose regime imposed by a fictional drug cartel poses a threat to the security of Northamerica. Meanwhile, a homogeneous view of Latin America is used.